2021
DOI: 10.1123/ijsnem.2020-0374
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hydration Factors Over the Course of Heat Acclimation in Endurance Athletes

Abstract: The purpose of this study was to examine the effect of heat acclimation (HA) on thirst levels, sweat rate, and percentage of body mass loss (%BML), and changes in fluid intake factors throughout HA induction. Twenty-eight male endurance athletes (mean ± SD; age, 35 ± 12 years; body mass, 73.0 ± 8.9 kg; maximal oxygen consumption, 57.4 ± 6.8 ml·kg−1·min−1) completed 60 min of exercise in a euhydrated state at 58.9 ± 2.3% velocity of maximal oxygen consumption in the heat (ambient temperature, 35.0 ± 1.3 °C; rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Perceived thirst is the only outcome that has been observed to be reduced after repeated exposures to hypohydration. This is the first study to report such an observation in the current research context; however, a recent study has reported a moderate reduction in perceived thirst after heat acclimation with ad libitum fluid intake [51]. Surprisingly, perceived thirst was reduced while the magnitude of change in plasma volume and plasma osmolality during exercise remained similar through training.…”
Section: Impact Of Repeated Exposures To Low and Moderate Exercise-induced Hypohydration Levelsmentioning
confidence: 55%
“…Perceived thirst is the only outcome that has been observed to be reduced after repeated exposures to hypohydration. This is the first study to report such an observation in the current research context; however, a recent study has reported a moderate reduction in perceived thirst after heat acclimation with ad libitum fluid intake [51]. Surprisingly, perceived thirst was reduced while the magnitude of change in plasma volume and plasma osmolality during exercise remained similar through training.…”
Section: Impact Of Repeated Exposures To Low and Moderate Exercise-induced Hypohydration Levelsmentioning
confidence: 55%
“…As previously mentioned, these data were part of a larger study that specifically investigated the physiological effects occurring in HR, Trec, and sweat rate (SR) as well as the performance measures, and more detailed analyses can be found in [ 22 , 23 , 24 , 25 , 26 ]. The average duration of exercise during each HAz session was 56.38 ± 72.66 min for the running sessions and 91.67 ± 69.27 min for the cycling sessions.…”
Section: Resultsmentioning
confidence: 99%
“…This study took place in <<removed for review>>. Data presented within this manuscript are part of a larger study that focused on physiological and performance measures relative to this heat training protocol; however, the current study investigated different hypotheses and data focusing on environmental stress symptoms reported in the ESQ before and after heat stress trials during HAz, HA, and HT [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following an explanation of study procedures, which were approved by the Institutional Review Board (IRB) at The University of Connecticut, participants provided informed written consent to participate in this study. This study is a part of a large research study, and other research questions are answered in other manuscripts [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%